Coil design for the straight field line mirror - Ågren, O.; Moiseenko, V.Е. (Problems of Atomic Science and Technology, 2022)
This paper briefly describes numerical design of 3D super-conduction coils aimed to mimic analytically derived magnetic field for the Straight Field Line Mirror (SFLM) concept. The paper is based on a manuscript for a previous IAEA report, i.e. IAEA-TECDOC-1998.